Molecular Mechanism Underlying Derepressed Male Production in Hexaploid Persimmon - Masuda, Kanae; Fujita, Naoko; Yang, Ho-Wen; Ushijima, Koichiro; Kubo, Yasutaka; Tao, Ryutaro; Akagi, Takashi (Frontiers in Plant Science, 2020)
Sex expression in plants is often flexible and contributes to the maintenance of genetic diversity within a species. In diploid persimmons (the genus Diospyros), the sexuality is controlled by the Y chromosome-encoded small-RNA gene, OGI, and its autosomal counterpart, MeGI. Hexaploid Oriental persimmon (D. kaki) evolved more flexible sex expression, where genetically male individuals carrying OGI, can produce both male and female flowers (monoecy). This is due to (semi-)inactivation of OGI by the Kali-SINE retrotransposon insertion on the promoter region and the resultant DNA methylations. Instead, flower sex determination in Oriental persimmon is also dependent on DNA methylation states of MeGI. Here, we focused on a cultivar, Kumemaru, which shows stable male flower production. Our results demonstrated that cv. Kumemaru carries OGI with Kali-SINE which was highly methylated as well as in other monoecious cultivars; nevertheless, OGI gene could have a basal expression level. Transcriptomic analysis between cv. Kumemaru and 14 cultivars that predominantly produce female flowers, showed differentially expressed genes specific to cv. Kumemaru, which is mainly involved in stress responses. Co-expression gene networks focusing on the DEGs also suggested the involvement of stress signals, mainly via gibberellin (GA), salicylic acid (SA), and especially jasmonic acid (JA) signal pathways. We also identified potential regulators of this co-expression module, represented by the TCP4 transcription factor. Furthermore, we attempted to identify cv. Kumemaru-specific transcripts polymorphisms potentially contributing to derepressed OGI expression, by cataloging subsequences (k-mers) in the transcriptomic reads from cv. Kumemaru and the other 14 female cultivars. Overall, although the direct genetic factor to activate OGI remains to be solved, our results implied the involvement of stress signals in the release of silenced OGI and the resultant continuous male production.